PERANCANGAN SISTEM INFORMASI PELAYANAN PARKIR KENDARAAN RUMAH SAKIT UMUM KABUPATEN MAJENE - Sudirman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The aim of this research is that he had to devise a system based on data parking Majene district general hospital. The method is applicable in the interview obervasi, documentation,and reviewske pustakaan. Software used to manufacture these information systems that of Microsoft Access 2007,Adobe Photoshop CS versions 5 and Microsoft Visual Basic 6.0. Data processing the parking lot is a major activity transportation department Majene the staff parked on duty in district general hospital Majene. In the ongoing make less optimal services, because the officers to record data parking a vehicleon the books, so often finds it difficult to do sums in parking rates, and there are still behind with the accesories vehicle, and vehicles and the staff parked usually irresponsibly. The information is based on expectations in order to simplify the registration and officers in data search parking because all the data stored in a database.